Solar light responsive ZnO nanoparticles adjusted using Cd and La Co-dopant photodetector - Gozeh, Bestoon Anwer; Karabulut, Abdulkerim; Yildiz, Abdulkadir; Yakuphanoğlu, Fahrettin (Elsevier Science Sa, 2018)
Optical sensing from the solar light range of light is very important for industrial process monitoring and life science. Hence, we present inorganic photodetector, operating between 200 and 1200 nm wavelength invented (Cd0.1/xLa co-doped ZnO, x = 0.1, 0.5, 2, and 4 wt%) nanoparticles thin films were synthesis onto p-Si and glass substrates by the Sol-gel spin coating technique. The films indicate that a high transmittance about 92% in the visible region. The optical bandgap of the thin films was used optical data demonstrated that the band gap of the films decreased with dopant concentration. The surface morphology and elemental compositions were investigated by SEM and EDX. The diodes exhibited high photocurrent responsivity under various illuminations. Herein, from I-V characteristics determined the electronic parameters such as ideality factor, barrier height and series resistance. The C-V and G-V of the diodes were investigated in the range of 10-1000 kHz. Moreover, an approach to improve the Ion/Ioff ratio (photoresponse) by modifying the concentration has been investigated under dark and light illuminations, respectively. The Al/p-type-Si/Cd-(0.1)-La((0.1))Wt/Al photodetector exhibited a highest photoresponse were found to be 2263. Finally, the interface states were determined to explain the results obtained in the present study. The obtained results suggest that Cd/La-co-doped ZnO/p-Si diodes can be enhanced and pave the way for its potential application in the optoelectronic devices e.g. photodetectors. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Co-doped ZnO; Sol-gel; Electrical properties; Photodetector